An intumescent nanometer flame retardant, a preparation method and application thereof

CN117430871BActive Publication Date: 2026-10-16ELECTRIC POWER RESEARCH INSTITUTE OF STATE GRID SHANDONG ELECTRIC POWER COMPANY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311470768.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-06
Publication Date
2026-10-16
Estimated Expiration
2043-11-06

AI Technical Summary

Technical Problem

但是EP纳米复合材料往往无法通过常规的火灾安全性测试(如垂直燃烧试验),并且这些无机纳米材料容易在聚合物基体中发生团聚,易导致环氧树脂材料阻燃性能和力学性能的恶化

Benefits of technology

[0057] The present invention relates to an intumescent nano flame retardant containing a multi-layered core-shell structure, comprising two functional parts: a core of nano-SiO2 and an outer shell of intumescent organic layer. The outer shell acts as both a modifier for the nano-SiO2 particles and provides intumescent flame retardancy. The outer shell has a three-layer structure, including a nitrogen-containing organic layer ("gas source"), a hydroxyl-containing organic layer ("carbon source"), and a phosphorus-containing organic layer ("acid source").

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117430871B_ABST
    Figure CN117430871B_ABST
Patent Text Reader

Abstract

The application discloses an intumescent nano flame retardant and a preparation method and application thereof, and relates to the technical field of flame retardants. The preparation method comprises the following steps: adding sodium hydroxide aqueous solution into a reaction system of SiO2 nanoparticles and cyanuric chloride while stirring, and performing a primary reaction after the addition is completed; adding a polyhydroxy organic compound into the reaction system after the primary reaction is completed, adding sodium hydroxide aqueous solution while stirring, and performing a secondary reaction to obtain modified nanoparticles; adding triethylamine into a mixed solution of the modified nanoparticles and MeP-Cl to perform a tertiary reaction; and obtaining the intumescent nano flame retardant through cleaning and drying of a reaction product. The intumescent nano flame retardant has SiO2 as a core, an intumescent organic layer composed of three functional structures of a gas source, a carbon source and an acid source as a shell, has a multi-collaborative flame-retardant effect, solves the problems of easy aggregation and poor dispersibility of SiO2 in an epoxy resin material, avoids the problems of uneven mixing ratio and easy migration and precipitation of a traditional organic intumescent flame retardant, and can endow the epoxy resin material with high flame retardance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of flame retardant technology, specifically relating to an intumescent nano flame retardant, its preparation method, and its application. Background Technology

[0002] The statements herein provide only background information in relation to this invention and do not necessarily constitute prior art.

[0003] As an important thermosetting polymer, epoxy resin (EP) is widely used in coatings, electronic materials, adhesives, and composite materials. However, the flammability of epoxy resin has severely limited its further application in many fields; therefore, improving the flame retardant properties of epoxy resin is imperative. Halogen-free flame retardants, especially intumescent flame retardants (IFR), are widely used in the research of flame retardant properties of polymer materials due to their outstanding advantages such as high flame retardant efficiency, halogen-free nature, low smoke, and environmental friendliness.

[0004] Currently, widely used traditional intumescent flame retardants mainly achieve their flame-retardant effect by adding an acid source, a carbon source, and a gas source—a "three-source" approach—to the polymer matrix. The flame-retardant mechanism involves the acid source catalyzing the carbon source and polymer material to form char during combustion, while the gas source decomposes to produce non-flammable gases and expands the char layer, ultimately forming an expanded char layer with heat insulation and oxygen barrier properties. However, this method inevitably brings serious negative impacts, such as uneven mixing ratios of the "three sources," flame retardant migration, and low flame-retardant efficiency. It also leads to the deterioration of the mechanical properties of epoxy resin materials, resulting in poor overall performance.

[0005] In recent years, inorganic nanomaterials such as titanium dioxide, silicon dioxide, halloysite, montmorillonite, graphene, and sepiolite have been widely used as environmentally friendly flame retardants in various polymer materials. However, EP nanocomposites often fail conventional fire safety tests (such as vertical burning tests), and these inorganic nanomaterials are prone to agglomeration in the polymer matrix, which can easily lead to the deterioration of the flame retardant and mechanical properties of epoxy resin materials. Summary of the Invention

[0006] To address the shortcomings of existing technologies, the purpose of this invention is to provide an intumescent nano flame retardant, its preparation method, and its application, thereby meeting the high-performance requirements of EP (expandable flame retardant) through the development of a multifunctional intumescent flame retardant.

[0007] To achieve the above objectives, the present invention is implemented through the following technical solution:

[0008] In a first aspect, the present invention provides a method for preparing an intumescent nano flame retardant, comprising the following steps:

[0009] Sodium hydroxide aqueous solution was added dropwise to the reaction system of SiO2 nanoparticles and cyanuric chloride while stirring. After the addition was complete, a first-order reaction was carried out.

[0010] After the first-stage reaction was completed, a polyhydroxy organic compound was added to the reaction system, and sodium hydroxide aqueous solution was added dropwise while stirring to carry out the second-stage reaction, thereby obtaining modified nanoparticles.

[0011] Triethylamine was added dropwise to a mixed solution of the modified nanoparticles and MeP-Cl to carry out a three-stage reaction. The reaction product was washed and dried to obtain an intumescent nano flame retardant.

[0012] MeP-Cl is an organic molecule containing phosphoric acid chloride, namely dimethyl chlorophosphate.

[0013] This invention selects nano-SiO2 as the core of an intumescent nano-flame retardant and a "three-source" intumescent organic layer as the outer shell. Nano-SiO2 has advantages such as high specific surface area and strong thermal stability, and its surface has abundant OH active groups, which can be used for chemical modification and functionalization.

[0014] In this invention, based on the high reactivity of P-Cl and C-Cl bonds, nitrogen-rich cyanuric chloride molecules with multiple active modification sites are grafted onto the SiO2 surface through a chemical reaction. The cyanuric chloride molecules can be used as a gas source for the intumescent nano flame retardant. Next, polyhydroxy organic compounds are grafted onto the triazine molecular structure. The polyhydroxy organic compounds can be used as a carbon source for the intumescent nano flame retardant. Finally, phosphorus-containing organic compounds are modified onto the outermost surface of the material through a reaction with surface hydroxyl groups. The phosphorus-containing organic compounds serve as an acid source for the intumescent nano flame retardant, ultimately realizing the construction of an intumescent nano flame retardant composed of nano SiO2 and a "three-source" intumescent organic layer.

[0015] This intumescent nano-flame retardant exhibits multiple synergistic flame retardant mechanisms during polymer combustion. Firstly, a PN synergistic effect exists between the acid source and the gas source, specifically as follows: the polyphosphoric acid formed by the decomposition of the acid source at high temperatures promotes the dehydration and char formation of the epoxy resin material, resulting in a char layer; nitrogen in the gas source can increase the thermal stability of the acid source by forming PN intermediates; simultaneously, the gas source can dilute the oxygen concentration in the combustion environment by releasing non-flammable gases, thus promoting the expansion of the char layer. Therefore, this synergistic effect between the acid source and the gas source promotes the formation of an expanded char layer with functions such as heat insulation, oxygen isolation, and inhibition of combustible gas release.

[0016] Secondly, there is a P-Si synergistic effect between the acid source and silicon dioxide, as follows: the acid source catalyzes the formation of the heat-insulating carbon layer. Due to the low surface energy of silicon, silicon dioxide can easily migrate to the surface of the material to be modified for flame retardancy to form a silicon-containing protective layer, which further improves the thermal stability of the carbon layer, thereby exerting the P-Si synergistic flame retardant effect.

[0017] Finally, there is a P-OH synergistic effect between the acid source and the carbon source, as follows: On the one hand, the acid source enhances the thermal stability of the acid source by undergoing a phosphorylation reaction with hydroxyl groups; on the other hand, the acid source can catalyze the carbonization of the carbon source, further enhancing the residual carbon rate of the expanded carbon layer, so that the expanded carbon layer has better heat insulation, oxygen isolation, and combustible gas release inhibition properties.

[0018] Therefore, the design based on chemically modified SiO2 with an intumescent organic layer solves the problems of easy agglomeration and poor dispersibility of SiO2 nanoparticles in epoxy resin materials. Moreover, the three-in-one intumescent organic layer can also solve the problems of uneven mixing ratio and easy migration and precipitation of traditional organic intumescent flame retardants, thus endowing epoxy resin materials with high flame retardancy.

[0019] In addition, the preparation process of this flame retardant is simple, environmentally friendly, requires no complicated post-processing, and is easy to industrialize.

[0020] In some embodiments, the mass ratio of cyanuric chloride to SiO2 in the primary reaction is 0.1-0.3:1, including but not limited to 0.11:1, 0.13:1, 0.14:1, 0.15:1, 0.17:1, 0.18:1, 0.2:1, 0.21:1, 0.23:1, 0.25:1, 0.27:1, 0.3:1, etc.

[0021] In some embodiments, the molar ratio of sodium hydroxide to cyanuric chloride in the first-order reaction is 1:0.8-1.2. This includes, but is not limited to, 1:0.81, 1:0.83, 1:0.87, 1:0.89, 1:0.91, 1:0.95, 1:0.97, 1:0.99, 1:1, 1:12, 1:16, 1:18, 1:2, etc.

[0022] Preferably, in the first-order reaction, the volume of the sodium hydroxide aqueous solution is 5%-20% of the volume of the organic solvent in the reaction system.

[0023] More preferably, the organic solvent in the reaction system is selected from acetonitrile, dioxane, dimethylformamide (DMF), or xylene.

[0024] In a further preferred embodiment, the amount of the organic solvent added is 5-10 times the total weight of cyanuric chloride and SiO2.

[0025] In some embodiments, the primary reaction temperature is 70-110℃, and the reaction time is 6-12 hours. The primary reaction temperature includes, but is not limited to, 70℃, 72℃, 75℃, 80℃, 83℃, 85℃, 86℃, 89℃, 90℃, 93℃, 94℃, 97℃, 100℃, 101℃, 104℃, 105℃, 106℃, and 110℃.

[0026] The reaction time for a first-order reaction includes, but is not limited to, 6h, 7h, 8h, 9h, 10h, 11h, 12h, etc.

[0027] In some embodiments, the polyhydroxy organic compound is selected from one or a combination of glycerol, pentaerythritol, dipentaerythritol, or glucose.

[0028] Preferably, the molar ratio of the polyhydroxy organic compound to cyanuric chloride is 1.5-2.5:1. This includes, but is not limited to, 1.5:1, 1.7:1, 1.9:1, 2:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, etc.

[0029] Preferably, in the secondary reaction, the molar ratio of sodium hydroxide to cyanuric chloride is 1.5-2.5:1. The amount of sodium hydroxide added is based on the amount of cyanuric chloride added.

[0030] Preferably, in the secondary reaction, the volume of the added sodium hydroxide aqueous solution is 5%-20% of the volume of the organic solvent in the reaction system.

[0031] In some embodiments, the secondary reaction temperature is 70-110°C and the reaction time is 6-12 hours.

[0032] The reaction temperature includes, but is not limited to, 70℃, 75℃, 80℃, 85℃, 90℃, 95℃, 100℃, 105℃, 110℃, etc.

[0033] Reaction times include, but are not limited to, 6h, 8h, 10h, 11h, 12h, etc.

[0034] In some embodiments, in the third-order reaction, the solvent used in the mixed solution is selected from one or a combination of acetonitrile, chloroform, xylene, or dioxane.

[0035] In some embodiments, the molar ratio of MeP-Cl, triethylamine, and polyhydroxy organic compounds is 1:0.8-1.2:0.8-1.2.

[0036] In some embodiments, the reaction temperature of the tertiary reaction is 20-30°C, and the reaction time is 8-12 hours.

[0037] The reaction temperature includes, but is not limited to, 20℃, 22℃, 24℃, 26℃, 28℃, 30℃, etc.

[0038] Reaction times include, but are not limited to, 8h, 9h, 10h, 11h, 12h, etc.

[0039] In some embodiments, the reaction products are washed with ethanol.

[0040] Preferably, the reaction product is dried at 65-80°C after washing.

[0041] Secondly, the present invention provides an intumescent nano flame retardant prepared by the aforementioned preparation method.

[0042] In some embodiments, the intumescent nano flame retardant comprises, from the inside out, a nano SiO2 core, a nitrogen-containing organic layer, a hydroxyl-containing organic layer, and a phosphorus-containing organic layer as the outer shell.

[0043] Preferably, the average particle size of the nano-SiO2 core is 50 nm.

[0044] Preferably, the nitrogen-containing organic layer is a triazine-based organic compound.

[0045] Preferably, the hydroxyl-containing organic layer is a polyhydroxy organic compound.

[0046] Preferably, the phosphorus-containing organic layer is an organophosphate.

[0047] Thirdly, the present invention provides a flame-retardant polymer composite material, comprising: the intumescent nano flame retardant and a polymer, wherein the intumescent nano flame retardant has a mass percentage of 1-15 wt%. This includes, but is not limited to, 1 wt%, 3 wt%, 5 wt%, 8 wt%, 10 wt%, 12 wt%, 14 wt%, 15 wt%, etc.

[0048] In some embodiments, the polymer is an epoxy resin.

[0049] Fourthly, the present invention provides a method for preparing the flame-retardant polymer composite material, comprising the following steps:

[0050] Weigh the epoxy resin, curing agent, and intumescent nano flame retardant according to the specified proportions.

[0051] Add the intumescent nano flame retardant to the epoxy resin at 100-115℃, mix well, remove air bubbles under vacuum to obtain the primary mixture.

[0052] Add the curing agent to the primary mixture at 100-115℃ and mix well to obtain the secondary mixture;

[0053] The secondary mixture is injected into a mold and heated to solidify, thus obtaining the final product.

[0054] In some embodiments, the heat curing involves first curing at 80-100℃ for 1-3 hours, and then controlling the heating temperature at 140-150℃ for a second curing of 4-8 hours.

[0055] This invention uses an intumescent nano flame retardant to modify epoxy resin. The modified epoxy resin has a UL-94 vertical flammability rating of V-0 and an LOI of 32.7%.

[0056] The beneficial effects achieved by one or more embodiments of the present invention described above are as follows:

[0057] The present invention relates to an intumescent nano flame retardant containing a multi-layered core-shell structure, comprising two functional parts: a core of nano-SiO2 and an outer shell of intumescent organic layer. The outer shell acts as both a modifier for the nano-SiO2 particles and provides intumescent flame retardancy. The outer shell has a three-layer structure, including a nitrogen-containing organic layer ("gas source"), a hydroxyl-containing organic layer ("carbon source"), and a phosphorus-containing organic layer ("acid source").

[0058] The single flame retardant prepared by this invention combines gas, carbon, and acid sources. By chemically coating nano-SiO2 with these sources, aggregation of nano-SiO2 can be effectively prevented. Furthermore, the loading of the gas, carbon, and acid sources on the single nano-SiO2 is controllable and relatively uniform, ensuring that the gas, carbon, and acid sources are also uniformly dispersed based on the uniform dispersion of nano-SiO2. This overcomes the shortcomings of traditional intumescent flame retardants, such as uneven mixing ratios and easy migration in multi-system mixtures. The synthesis process of the flame retardant of this invention is simple, the product is easy to post-process, and it is easy to control and industrialize.

[0059] The core-shell structure composed of nano-SiO2 and an intumescent organic layer exhibits a synergistic flame-retardant effect, endowing the intumescent nano-flame retardant with high heat resistance and high flame retardancy. When the intumescent nano-flame retardant is added to epoxy resin materials, at high temperatures, the flame retardant releases gases and the catalyst phosphoric acid. Its rich polyhydroxy structure also participates in the char formation reaction, becoming part of the char layer, effectively enhancing the formation of the intumescent char layer and the char residue rate, thus significantly improving the flame-retardant properties of epoxy resins and other materials. Nano-SiO2 also synergistically participates in enhancing the flame retardancy and mechanical properties of the intumescent layer surface. Furthermore, this flame retardant is a highly efficient, low-toxicity, halogen-free, and environmentally friendly flame retardant. Attached Figure Description

[0060] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.

[0061] Figure 1 This is a schematic diagram of the structure of an intumescent nano flame retardant prepared in Example 1 of the present invention;

[0062] Figure 2 The infrared spectrum of an intumescent nano flame retardant prepared in Example 1 of this invention;

[0063] Figure 3Thermogravimetric analysis (TGA) of an intumescent nano flame retardant prepared in Example 1 of this invention. Detailed Implementation

[0064] It should be noted that the following detailed description is illustrative and intended to provide further explanation of the invention. Unless otherwise specified, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.

[0065] In this invention, a three-in-one intumescent nano flame retardant is constructed by using nano-silica as the core of an intumescent nano flame retardant and an intumescent organic layer composed of nitrogen-containing organic compounds, polyhydroxy organic compounds, and phosphorus-containing organic compounds as the outer shell. This intumescent nano flame retardant is then used to modify epoxy resin materials to enhance their flame retardant properties.

[0066] The present invention will be further described below with reference to the embodiments.

[0067] (I) Examples of flame retardant synthesis of the present invention are as follows:

[0068] Example 1

[0069] S1. Add 5.0g nano SiO2, 1.0g cyanuric chloride and 100ml dioxane to a three-necked flask, reflux and stir at 100℃, then add dropwise an aqueous solution (10ml) containing 0.22g sodium hydroxide, and continue stirring at 100℃ for 8h.

[0070] S2. Add 1.0 g of glycerol to the above reaction system, and then add dropwise 10 ml of an aqueous solution containing 0.43 g of sodium hydroxide at 100 °C. Continue stirring at 100 °C for 10 h. After the reaction is complete, remove the solvent by filtration to obtain a white solid, wash three times with deionized water and ethanol, dry in an oven at 70 °C, and grind for later use.

[0071] S3. Add the solid obtained in step S2 and 2.0 g of MeP-Cl to xylene, and add 1.1 g of triethylamine dropwise while stirring at room temperature, and continue the reaction for 12 h. After the reaction is completed, remove the solvent by filtration to obtain a white solid, wash three times with deionized water and ethanol, dry in an oven at 70 °C, and grind for later use.

[0072] Example 1 Performance Test:

[0073] (1) Infrared spectral analysis was performed on the nano flame retardant prepared in Example 1 of the present invention. See details below. Figure 2 .

[0074] The figure shows that the characteristic peak of the infrared spectrum of the nano flame retardant is at 1080 cm⁻¹. -1 (Si-O-Si stretching vibration) is consistent with SiO2, at 1294 cm⁻¹.-1 (P=O stretching vibration), 1007cm -1 (POC stretching vibration) is consistent with that of the raw material MeP-Cl, at 1470 cm⁻¹. -1 The (C=N stretching vibration) is consistent with that of the raw material cyanuric chloride, which suggests that the intumescent nano flame retardant composed of nano-silica and an intumescent organic layer has been successfully prepared.

[0075] (2) The nano flame retardant prepared in Example 1 of this invention was subjected to thermogravimetric analysis (TGA), as detailed in the figure. Figure 3 .Depend on Figure 3 It can be seen that at 800℃, the remaining weights of unmodified SiO2 and intumescent nano flame retardant were 91.81% and 83.60%, respectively, with a mass change of 8.21% before and after modification, indicating that the chemical modification of the intumescent organic layer on the SiO2 surface was successfully achieved.

[0076] Example 2

[0077] S1. Add 5.0g nano SiO2, 1.0g cyanuric chloride and 100ml dioxane to a three-necked flask, reflux and stir at 100℃, then add dropwise an aqueous solution (10ml) containing 0.22g sodium hydroxide, and continue stirring at 100℃ for 8h.

[0078] S2. Add 1.48 g pentaerythritol to the above reaction system, and then add dropwise 10 ml of an aqueous solution containing 0.43 g sodium hydroxide at 100 °C. Continue stirring at 100 °C for 10 h. After the reaction is complete, remove the solvent by filtration to obtain a white solid, wash three times with deionized water and ethanol, dry in an oven at 70 °C, and grind for later use.

[0079] S3. Add the solid obtained in step S2 and 2.0 g of MeP-Cl to xylene, and add 1.1 g of triethylamine dropwise while stirring at room temperature, and continue the reaction for 12 h. After the reaction is completed, remove the solvent by filtration to obtain a white solid, wash three times with deionized water and ethanol, dry in an oven at 70 °C, and grind for later use.

[0080] Example 3

[0081] S1. Add 5.0g nano SiO2, 1.0g cyanuric chloride and 100ml dioxane to a three-necked flask, reflux and stir at 100℃, then add dropwise an aqueous solution (10ml) containing 0.22g sodium hydroxide, and continue stirring at 100℃ for 8h.

[0082] S2. Add 2.76 g of dipentaerythritol to the above reaction system, and then add dropwise 10 ml of an aqueous solution containing 0.43 g of sodium hydroxide at 100 °C. Continue stirring at 100 °C for 10 h. After the reaction is complete, remove the solvent by filtration to obtain a white solid, wash three times with deionized water and ethanol, dry in an oven at 70 °C, and grind for later use.

[0083] S3. Add the solid obtained in step S2 and 2.0 g of MeP-Cl to xylene, and add 1.1 g of triethylamine dropwise while stirring at room temperature, and continue the reaction for 12 h. After the reaction is completed, remove the solvent by filtration to obtain a white solid, wash three times with deionized water and ethanol, dry in an oven at 70 °C, and grind for later use.

[0084] Example 4

[0085] S1. Add 5.0g nano SiO2, 1.0g cyanuric chloride and 100ml dioxane to a three-necked flask, reflux and stir at 100℃, then add dropwise an aqueous solution (10ml) containing 0.22g sodium hydroxide, and continue stirring at 100℃ for 8h.

[0086] S2. Add 1.95g of glucose to the above reaction system, and then add 10ml of an aqueous solution containing 0.43g of sodium hydroxide dropwise at 100℃. Continue stirring at 100℃ for 10h. After the reaction is complete, remove the solvent by filtration to obtain a white solid, wash three times with deionized water and ethanol, dry in an oven at 70℃, and grind for later use.

[0087] S3. Add the solid obtained in step S2 and 2.0 g of MeP-Cl to xylene, and add 1.1 g of triethylamine dropwise while stirring at room temperature, and continue the reaction for 12 h. After the reaction is completed, remove the solvent by filtration to obtain a white solid, wash three times with deionized water and ethanol, dry in an oven at 70 °C, and grind for later use.

[0088] Example 5

[0089] S1. Add 4.5g nano SiO2, 1.0g cyanuric chloride and 130ml acetonitrile to a three-necked flask, reflux and stir at 80℃, then add dropwise an aqueous solution (13ml) containing 0.22g sodium hydroxide, and continue stirring at 80℃ for 10h.

[0090] S2. Add 1.0 g of glycerol to the above reaction system, and then add dropwise 13 ml of an aqueous solution containing 0.43 g of sodium hydroxide at 80 °C. Continue stirring at 80 °C for 10 h. After the reaction is complete, remove the solvent by filtration to obtain a white solid, wash three times with deionized water and ethanol, dry in an oven at 70 °C, and grind for later use.

[0091] S3. Add the solid obtained in step S2 and 2.0 g of MeP-Cl to xylene, and add 1.1 g of triethylamine dropwise while stirring at room temperature, and continue the reaction for 12 h. After the reaction is completed, remove the solvent by filtration to obtain a white solid, wash three times with deionized water and ethanol, dry in an oven at 70 °C, and grind for later use.

[0092] Example 6

[0093] S1. Add 4.5g nano SiO2, 1.0g cyanuric chloride and 130ml acetonitrile to a three-necked flask, reflux and stir at 100℃, then add dropwise an aqueous solution (13ml) containing 0.22g sodium hydroxide, and continue stirring at 100℃ for 8h.

[0094] S2. Add 1.48 g pentaerythritol to the above reaction system, and then add dropwise 13 ml of an aqueous solution containing 0.43 g sodium hydroxide at 100 °C. Continue stirring at 100 °C for 10 h. After the reaction is complete, remove the solvent by filtration to obtain a white solid, wash three times with deionized water and ethanol, dry in an oven at 70 °C, and grind for later use.

[0095] S3. Add the solid obtained in step S2 and 2.0 g of MeP-Cl to xylene, and add 1.1 g of triethylamine dropwise while stirring at room temperature, and continue the reaction for 12 h. After the reaction is completed, remove the solvent by filtration to obtain a white solid, wash three times with deionized water and ethanol, dry in an oven at 70 °C, and grind for later use.

[0096] Example 7

[0097] S1. Add 4.5g nano SiO2, 1.0g cyanuric chloride and 130ml acetonitrile to a three-necked flask, reflux and stir at 100℃, then add dropwise an aqueous solution (13ml) containing 0.22g sodium hydroxide, and continue stirring at 100℃ for 10h.

[0098] S2. Add 2.76 g of dipentaerythritol to the above reaction system, and then add dropwise 13 ml of an aqueous solution containing 0.43 g of sodium hydroxide at 100 °C. Continue stirring at 100 °C for 10 h. After the reaction is complete, remove the solvent by filtration to obtain a white solid, wash three times with deionized water and ethanol, dry in an oven at 70 °C, and grind for later use.

[0099] S3. Add the solid obtained in step S2 and 2.0 g of MeP-Cl to xylene, and add 1.1 g of triethylamine dropwise while stirring at room temperature, and continue the reaction for 12 h. After the reaction is completed, remove the solvent by filtration to obtain a white solid, wash three times with deionized water and ethanol, dry in an oven at 70 °C, and grind for later use.

[0100] Example 8

[0101] S1. Add 4.5g nano SiO2, 1.0g cyanuric chloride and 130ml acetonitrile to a three-necked flask, reflux and stir at 100℃, then add dropwise an aqueous solution (13ml) containing 0.22g sodium hydroxide, and continue stirring at 100℃ for 12h.

[0102] S2. Add 1.95g of glucose to the above reaction system, and then add 13ml of an aqueous solution containing 0.43g of sodium hydroxide dropwise at 100℃. Continue stirring at 100℃ for 10h. After the reaction is complete, remove the solvent by filtration to obtain a white solid, wash three times with deionized water and ethanol, dry in an oven at 70℃, and grind for later use.

[0103] S3. Add the solid obtained in step S2 and 2.0 g of MeP-Cl to xylene, and add 1.1 g of triethylamine dropwise while stirring at room temperature, and continue the reaction for 12 h. After the reaction is completed, remove the solvent by filtration to obtain a white solid, wash three times with deionized water and ethanol, dry in an oven at 70 °C, and grind for later use.

[0104] Example 9

[0105] S1. Add 4.0g nano SiO2, 1.0g cyanuric chloride and 120ml dimethylformamide to a three-necked flask, reflux and stir at 110℃, then add dropwise an aqueous solution (10ml) containing 0.25g sodium hydroxide, and continue stirring at 110℃ for 10h.

[0106] S2. Add 1.0 g of glycerol to the above reaction system, and then add dropwise 10 ml of an aqueous solution containing 0.43 g of sodium hydroxide at 80 °C. Continue stirring at 100 °C for 10 h. After the reaction is complete, remove the solvent by filtration to obtain a white solid, wash three times with deionized water and ethanol, dry in an oven at 70 °C, and grind for later use.

[0107] S3. Add the solid obtained in step S2 and 2.0 g of MeP-Cl to xylene, and add 1.1 g of triethylamine dropwise while stirring at room temperature, and continue the reaction for 8 h. After the reaction is completed, remove the solvent by filtration to obtain a white solid, wash three times with deionized water and ethanol, dry in an oven at 70 °C, and grind for later use.

[0108] Example 10

[0109] S1. Add 4.0g nano SiO2, 1.0g cyanuric chloride and 100ml dimethylformamide to a three-necked flask, reflux and stir at 80℃, then add dropwise an aqueous solution (10ml) containing 0.22g sodium hydroxide, and continue stirring at 80℃ for 6h.

[0110] S2. Add 1.54 g pentaerythritol to the above reaction system, and then add dropwise 10 ml of an aqueous solution containing 0.43 g sodium hydroxide at 80 °C. Continue stirring at 100 °C for 10 h. After the reaction is complete, remove the solvent by filtration to obtain a white solid, wash three times with deionized water and ethanol, dry in an oven at 70 °C, and grind for later use.

[0111] S3. Add the solid obtained in step S2 and 2.0 g of MeP-Cl to xylene, and add 1.3 g of triethylamine dropwise while stirring at room temperature, and continue the reaction for 8 h. After the reaction is completed, remove the solvent by filtration to obtain a white solid, wash three times with deionized water and ethanol, dry in an oven at 70 °C, and grind for later use.

[0112] Example 11

[0113] S1. Add 5.0g nano SiO2, 1.0g cyanuric chloride and 100ml dimethylformamide to a three-necked flask, reflux and stir at 90℃, then add dropwise an aqueous solution (10ml) containing 0.22g sodium hydroxide, and continue stirring at 90℃ for 8h.

[0114] S2. Add 2.81 g of dipentaerythritol to the above reaction system, and then add dropwise 10 ml of an aqueous solution containing 0.43 g of sodium hydroxide at 100 °C. Continue stirring at 105 °C for 10 h. After the reaction is complete, remove the solvent by filtration to obtain a white solid, wash three times with deionized water and ethanol, dry in an oven at 70 °C, and grind for later use.

[0115] S3. Add the solid obtained in step S2 and 2.0 g of MeP-Cl to xylene, and add 1.05 g of triethylamine dropwise while stirring at room temperature, and continue the reaction for 10 h. After the reaction is completed, remove the solvent by filtration to obtain a white solid, wash three times with deionized water and ethanol, dry in an oven at 70 °C, and grind for later use.

[0116] Example 12

[0117] S1. Add 5.0g nano SiO2, 1.0g cyanuric chloride and 100ml dimethylformamide to a three-necked flask, reflux and stir at 80℃, then add dropwise an aqueous solution (10ml) containing 0.22g sodium hydroxide, and continue stirring at 80℃ for 12h.

[0118] S2. Add 1.83g of glucose to the above reaction system, and then add dropwise 10ml of an aqueous solution containing 0.43g of sodium hydroxide at 100℃. Continue stirring at 70℃ for 12h. After the reaction is complete, remove the solvent by filtration to obtain a white solid, wash three times with deionized water and ethanol, dry in a 70℃ oven, and grind for later use.

[0119] S3. Add the solid obtained in step S2 and 2.0 g of MeP-Cl to xylene, and add 1.1 g of triethylamine dropwise while stirring at room temperature, and continue the reaction for 12 h. After the reaction is completed, remove the solvent by filtration to obtain a white solid, wash three times with deionized water and ethanol, dry in an oven at 70 °C, and grind for later use.

[0120] Example 13

[0121] S1. Add 5.0g nano SiO2, 1.0g cyanuric chloride and 100ml xylene to a three-necked flask, reflux and stir at 95℃, then add dropwise an aqueous solution (10ml) containing 0.22g sodium hydroxide, and continue stirring at 95℃ for 8h.

[0122] S2. Add 1.2 g of glycerol to the above reaction system, and then add dropwise 10 ml of an aqueous solution containing 0.46 g of sodium hydroxide at 100 °C. Continue stirring at 105 °C for 8 h. After the reaction is complete, remove the solvent by filtration to obtain a white solid, wash three times with deionized water and ethanol, dry in an oven at 70 °C, and grind for later use.

[0123] S3. Add the solid obtained in step S2 and 2.0 g of MeP-Cl to xylene, and add 1.1 g of triethylamine dropwise while stirring at room temperature, and continue the reaction for 12 h. After the reaction is completed, remove the solvent by filtration to obtain a white solid, wash three times with deionized water and ethanol, dry in an oven at 70 °C, and grind for later use.

[0124] Example 14

[0125] S1. Add 5.0g nano SiO2, 1.0g cyanuric chloride and 100ml xylene to a three-necked flask, reflux and stir at 100℃, then add dropwise an aqueous solution (10ml) containing 0.22g sodium hydroxide, and continue stirring at 100℃ for 8h.

[0126] S2. Add 1.62 g pentaerythritol to the above reaction system, and then add dropwise 10 ml of an aqueous solution containing 0.43 g sodium hydroxide at 100 °C. Continue stirring at 90 °C for 12 h. After the reaction is complete, remove the solvent by filtration to obtain a white solid, wash three times with deionized water and ethanol, dry in an oven at 70 °C, and grind for later use.

[0127] S3. Add the solid obtained in step S2 and 2.0 g of MeP-Cl to xylene, and add 1.1 g of triethylamine dropwise while stirring at room temperature, and continue the reaction for 8 h. After the reaction is completed, remove the solvent by filtration to obtain a white solid, wash three times with deionized water and ethanol, dry in an oven at 70 °C, and grind for later use.

[0128] Example 15

[0129] S1. Add 5.0g nano SiO2, 1.0g cyanuric chloride and 100ml xylene to a three-necked flask, reflux and stir at 105℃, then add dropwise an aqueous solution (10ml) containing 0.22g sodium hydroxide, and continue stirring at 105℃ for 9h.

[0130] S2. Add 2.75 g of dipentaerythritol to the above reaction system, and then add dropwise 10 ml of an aqueous solution containing 0.43 g of sodium hydroxide at 100 °C. Continue stirring at 95 °C for 10 h. After the reaction is complete, remove the solvent by filtration to obtain a white solid, wash three times with deionized water and ethanol, dry in an oven at 70 °C, and grind for later use.

[0131] S3. Add the solid obtained in step S2 and 2.0 g of MeP-Cl to xylene, and add 1.1 g of triethylamine dropwise while stirring at room temperature, and continue the reaction for 8 h. After the reaction is completed, remove the solvent by filtration to obtain a white solid, wash three times with deionized water and ethanol, dry in an oven at 70 °C, and grind for later use.

[0132] Example 16

[0133] S1. Add 5.0g nano SiO2, 1.0g cyanuric chloride and 100ml xylene to a three-necked flask, reflux and stir at 110℃, then add dropwise an aqueous solution (10ml) containing 0.22g sodium hydroxide, and continue stirring at 110℃ for 12h.

[0134] S2. Add 1.91 g of glucose to the above reaction system, and then add 10 ml of an aqueous solution containing 0.43 g of sodium hydroxide dropwise at 100 °C. Continue stirring at 75 °C for 6 h. After the reaction is complete, remove the solvent by filtration to obtain a white solid, wash three times with deionized water and ethanol, dry in an oven at 70 °C, and grind for later use.

[0135] S3. Add the solid obtained in step S2 and 2.0 g of MeP-Cl to xylene, and add 1.1 g of triethylamine dropwise while stirring at room temperature, and continue the reaction for 8 h. After the reaction is completed, remove the solvent by filtration to obtain a white solid, wash three times with deionized water and ethanol, dry in an oven at 70 °C, and grind for later use.

[0136] (II) Applying the intumescent nano flame retardant of the present invention to the preparation of epoxy resin materials

[0137] The intumescent nano-flame retardants obtained in Examples 1, 2, 3, and 4 were added to epoxy resin materials to prepare nano-epoxy composite materials. Specific examples are as follows:

[0138] Example 2.1

[0139] The preparation method of flame-retardant modified epoxy resin includes the following steps:

[0140] 1) Weigh 50g of epoxy resin, 12.9g of curing agent, and 3.3g of the intumescent nano flame retardant prepared in Example 1 according to the following mass ratio;

[0141] 2) Add the flame retardant to the epoxy resin at 110℃, stir evenly, and remove air bubbles by vacuuming to obtain the primary mixture.

[0142] 3) Add the curing agent to the primary mixture at 110℃ and stir rapidly to fully dissolve the curing agent into a homogeneous system to obtain the secondary mixture;

[0143] 4) Inject the secondary mixture into the mold, place it in the oven, first control the heating temperature to 80℃ and cure for 2 hours, then control the heating temperature to 150℃ and cure for 6 hours. After curing, let it cool naturally to room temperature to obtain flame-retardant modified epoxy resin.

[0144] Example 2.2

[0145] The preparation method of flame-retardant modified epoxy resin includes the following steps:

[0146] 1) Weigh 50g of epoxy resin, 12.9g of curing agent, and 3.3g of the intumescent nano flame retardant prepared in Example 2 according to the following mass ratio;

[0147] 2) Add the flame retardant to the epoxy resin at 110℃, stir evenly, and remove air bubbles by vacuuming to obtain the primary mixture.

[0148] 3) Add the curing agent to the primary mixture at 110℃ and stir rapidly to fully dissolve the curing agent into a homogeneous system to obtain the secondary mixture;

[0149] 4) Inject the secondary mixture into the mold, place it in the oven, first control the heating temperature to 80℃ and cure for 2 hours, then control the heating temperature to 150℃ and cure for 6 hours. After curing, let it cool naturally to room temperature to obtain flame-retardant modified epoxy resin.

[0150] Example 2.3

[0151] The preparation method of flame-retardant modified epoxy resin includes the following steps:

[0152] 1) Weigh 50g of epoxy resin, 12.9g of curing agent, and 3.3g of the intumescent nano flame retardant prepared in Example 3 according to the following mass ratio;

[0153] 2) Add the flame retardant to the epoxy resin at 110℃, stir evenly, and remove air bubbles by vacuuming to obtain the primary mixture.

[0154] 3) Add the curing agent to the primary mixture at 110℃ and stir rapidly to fully dissolve the curing agent into a homogeneous system to obtain the secondary mixture;

[0155] 4) Inject the secondary mixture into the mold, place it in the oven, first control the heating temperature to 80℃ and cure for 2 hours, then control the heating temperature to 150℃ and cure for 6 hours. After curing, let it cool naturally to room temperature to obtain flame-retardant modified epoxy resin.

[0156] Example 2.4

[0157] The preparation method of flame-retardant modified epoxy resin includes the following steps:

[0158] 1) Weigh 50g of epoxy resin, 12.9g of curing agent, and 3.3g of the intumescent nano flame retardant prepared in Example 4 according to the following mass ratio;

[0159] 2) Add the flame retardant to the epoxy resin at 110℃, stir evenly, and remove air bubbles by vacuuming to obtain the primary mixture.

[0160] 3) Add the curing agent to the primary mixture at 110℃ and stir rapidly to fully dissolve the curing agent into a homogeneous system to obtain the secondary mixture;

[0161] 4) Inject the secondary mixture into the mold, place it in the oven, first control the heating temperature to 80℃ and cure for 2 hours, then control the heating temperature to 150℃ and cure for 6 hours. After curing, let it cool naturally to room temperature to obtain flame-retardant modified epoxy resin.

[0162] Comparative Example

[0163] The preparation method includes the following steps:

[0164] 1) Weigh 50g of epoxy resin and 12.9g of curing agent according to the mass ratio of each component;

[0165] 2) Add the curing agent to the epoxy resin at 110℃ and stir rapidly to fully dissolve the curing agent into a homogeneous system;

[0166] 3) Pour the mixture from step 2) into the mold, place it in an oven, first control the heating temperature to 80℃ and cure for 2 hours, then control the heating temperature to 150℃ and cure for 6 hours. After curing, let it cool naturally to room temperature to obtain the final product.

[0167] The epoxy resin modified with the obtained flame retardant was subjected to limiting oxygen index and UL-94 vertical burning tests, and the results are shown in Table 1.

[0168] Table 1. Formulation and performance testing of epoxy resin materials modified with intumescent nano-flame retardants.

[0169]

[0170] In Table 1, The UL-94 rating is used to evaluate the flammability of materials, and its vertical burning test is conducted according to standard GB / T 2408- The test was conducted in 2008, and the specific steps were as follows:

[0171] 1) Clamp the top 6mm of the sample strip (130mm×13mm×13mm) with the vertical axis perpendicular, so that the bottom of the sample is 300mm above the horizontal cotton layer. The cotton layer is approximately 50mm×50mm×6mm in size.

[0172] 2) Place the blowtorch tube away from the sample and adjust the blowtorch to produce a test flame that meets the standard. Wait 5 minutes for the blowtorch to stabilize.

[0173] 3) Place the center of the flame at the midpoint of the bottom edge of the sample, while keeping the tip of the blowtorch 10 mm lower than this point, and hold for 10 seconds. After applying the flame to the sample for 10 seconds, immediately remove the blowtorch and start measuring the afterflame time t1 in seconds using a timing device.

[0174] 4) After the afterflame of the sample extinguishes, immediately place the test flame back under the sample, with the tip of the torch 10 mm below the bottom of the sample, and hold for 10 seconds. After applying the flame to the sample for the second time for 10 seconds, immediately remove the torch and simultaneously start measuring the afterflame time t2 and afterglow time t3 using a timing device. Also, observe and record whether any particles fall from the sample and whether they ignite the cotton pad.

[0175] The meanings of NR, V-0, V-1, and V-2 are as follows:

[0176] NR means no rating;

[0177] V-0: After two 10-second burning tests on the sample, the flame extinguishes within 10 seconds. After the second application of flame, the afterflame plus afterglow time of a single sample is no more than 30 seconds. No burning material falls or the burning material cannot ignite the cotton pad.

[0178] V-1: After two 10-second burning tests on the sample, the flame extinguishes within 30 seconds. After the second application of flame, the afterflame plus afterglow time of a single sample is no more than 60 seconds. No burning material falls or the burning material cannot ignite the cotton pad.

[0179] V-2: After two 10-second burning tests on the sample, the flame extinguishes within 30 seconds in both tests. After the second application of the flame, the afterflame plus afterglow time of a single sample is no more than 60 seconds. There is burning material falling or the burning material can ignite the cotton pad.

[0180] In Table 1, the limiting oxygen index refers to the oxygen-nitrogen mixture that, when introduced at 23℃±2℃, just sustains combustion of the material. Minimum oxygen concentration, expressed as a volume fraction, is used to evaluate the flame retardant properties of materials. Its oxygen index test method follows the standard. The testing is conducted according to GB / T2406.2-2009, and the specific steps are as follows:

[0181] 1) Prepare a sample with dimensions of 100mm×10mm×4mm and mark it 50mm away from the ignition end.

[0182] 2) Ignite the sample in air and observe its combustion. If the sample is found to burn unstablely in air, set the initial oxygen concentration of the test to about 21% (oxygen volume fraction).

[0183] 3) Ensure the combustion chamber is vertical. Install the sample vertically in the center of the combustion chamber, with the top of the sample at least 100 mm below the top opening of the combustion chamber, and the exposed part of the lowest point of the sample 100 mm above the top surface of the gas dispersion device on the combustion chamber base.

[0184] 4) Adjust the gas mixer and flow meter to mix the oxygen / nitrogen gases at 23℃±2℃, ensuring the oxygen concentration reaches the set value, and pass the gas through the combustion chamber at a flow rate of 40mm / s. Before igniting the sample, flush the combustion chamber with the mixed gas for at least 30 seconds to ensure the gas flow rate remains constant during ignition and sample combustion.

[0185] 5) Apply the lowest part of the flame to the top surface of the sample, or cover the entire top surface if necessary, but do not point the flame at the vertical surface of the sample. Apply the flame for 30 seconds, then remove it every 5 seconds, allowing sufficient time to observe whether the top surface of the sample is burning. After each additional 5 seconds, observe the entire top surface of the sample continuing to burn, then immediately remove the igniter. At this point, the sample is ignited, and you can begin recording the burning time and observing the burning length.

[0186] 6) If the test results of the sample meet the requirements of a combustion time of less than 180s and a combustion length of less than 50mm, increase the oxygen concentration. If the test results of the sample meet the requirements of a combustion time of more than 180s or a combustion length of more than 50mm, decrease the oxygen concentration, with each change in oxygen concentration being 0.2% of the total mixture.

[0187] 7) Remove the sample and clean the combustion chamber and igniter.

[0188] The test results of epoxy resin materials modified with different intumescent nano-flame retardants prepared in this embodiment are shown in Table 1. As can be seen from the table, compared with unmodified pure epoxy resin materials, the epoxy resin materials with 5% nano-flame retardant showed a significant improvement in flame retardant performance, with limiting oxygen indexes all above 29%, and the vertical burning test rating reaching V-0. These results indicate that the intumescent nano-flame retardant obtained by chemical covalent bonding of inorganic nanomaterials and an intumescent organic layer has a good synergistic effect of multiple flame retardants, which can endow epoxy resin materials with superior flame retardant properties.

[0189] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing an intumescent nano flame retardant, characterized in that: Includes the following steps: Sodium hydroxide aqueous solution was added dropwise to the reaction system of SiO2 nanoparticles and cyanuric chloride while stirring. After the addition was complete, a first-order reaction was carried out. After the first-stage reaction was completed, a polyhydroxy organic compound was added to the reaction system, and sodium hydroxide aqueous solution was added dropwise while stirring to carry out the second-stage reaction, thereby obtaining modified nanoparticles. Triethylamine was added dropwise to a mixed solution of the modified nanoparticles and dimethyl chlorophosphate to carry out a three-stage reaction. The reaction product was washed and dried to obtain an intumescent nano flame retardant. The polyhydroxy organic compound is selected from one or a combination of glycerol, pentaerythritol, dipentaerythritol, or glucose.

2. The preparation method of the intumescent nano flame retardant according to claim 1, characterized in that: The mass ratio of cyanuric chloride to SiO2 is 0.1-0.3:1; Alternatively, in the first-order reaction, the molar ratio of sodium hydroxide to cyanuric chloride is 1:0.8-1.

2.

3. The preparation method of the intumescent nano flame retardant according to claim 1, characterized in that: In the first-order reaction, the volume of the sodium hydroxide aqueous solution is 5%-20% of the volume of the organic solvent in the reaction system.

4. The preparation method of the intumescent nano flame retardant according to claim 3, characterized in that: The organic solvent in the reaction system is selected from acetonitrile, dioxane, dimethylformamide, or xylene.

5. The method for preparing the intumescent nano flame retardant according to claim 3, characterized in that: The amount of organic solvent added is 5-10 times the total weight of cyanuric chloride and SiO2.

6. The method for preparing the intumescent nano flame retardant according to claim 1, characterized in that: The first-stage reaction temperature is 70-110℃, and the reaction time is 6-12h; or the second-stage reaction temperature is 70-110℃, and the reaction time is 6-12h.

7. The method for preparing the intumescent nano flame retardant according to claim 1, characterized in that: The molar ratio of polyhydroxy organic compounds to cyanuric chloride is 1.5-2.5:

1.

8. The preparation method of the intumescent nano flame retardant according to claim 1, characterized in that: In the second-order reaction, the molar ratio of sodium hydroxide to cyanuric chloride is 1.5-2.5:

1.

9. The method for preparing the intumescent nano flame retardant according to claim 1, characterized in that: In the second-order reaction, the volume of the added sodium hydroxide aqueous solution is 5%-20% of the volume of the organic solvent in the reaction system.

10. The method for preparing the intumescent nano flame retardant according to claim 1, characterized in that: In the third-order reaction, the solvent used in the mixed solution is selected from one or a combination of acetonitrile, chloroform, xylene or dioxane; Alternatively, the molar ratio of dimethyl chlorophosphate, triethylamine, and polyhydroxy organic compounds is 1:0.8-1.2:0.8-1.2; Alternatively, the reaction temperature for a tertiary reaction is 20-30℃, and the reaction time is 8-12h.

11. The method for preparing the intumescent nano flame retardant according to claim 1, characterized in that: The reaction products were washed with ethanol.

12. The method for preparing the intumescent nano flame retardant according to claim 11, characterized in that: The reaction product is washed and then dried at 65-80℃.

13. An intumescent nano flame retardant, characterized in that: Prepared by any of the preparation methods described in claims 1-12.

14. The intumescent nano flame retardant according to claim 13, characterized in that: From the inside out, the outer shell of the expanded organic layer consists of a nano-SiO2 core, a nitrogen-containing organic layer, a hydroxyl-containing organic layer, and a phosphorus-containing organic layer.

15. The intumescent nano flame retardant according to claim 14, characterized in that: The average particle size of the nano-SiO2 core is 50 nm.

16. The intumescent nano flame retardant according to claim 14, characterized in that: The nitrogen-containing organic layer is a triazine-based organic compound.

17. The intumescent nano flame retardant according to claim 14, characterized in that: The hydroxyl-containing organic layer is a polyhydroxy organic compound.

18. The intumescent nano flame retardant according to claim 14, characterized in that: The phosphorus-containing organic layer is an organic phosphate ester.

19. A flame-retardant polymer composite material, characterized in that: The flame-retardant polymer composite material using the intumescent nano flame retardant according to any one of claims 13-18 comprises: the intumescent nano flame retardant and a polymer, wherein the intumescent nano flame retardant has a mass percentage of 1-15 wt%; and the polymer is an epoxy resin.

20. The method for preparing the flame-retardant polymer composite material according to claim 19, characterized in that: Includes the following steps: Weigh the epoxy resin, curing agent, and intumescent nano flame retardant according to the specified proportions. Add the intumescent nano flame retardant to the epoxy resin at 100-115℃, mix well, remove air bubbles under vacuum to obtain the primary mixture. Add the curing agent to the primary mixture at 100-115℃ and mix well to obtain the secondary mixture; The secondary mixture is injected into a mold and heated to solidify, thus obtaining the final product.

21. The preparation method according to claim 20, characterized in that: The heating and curing process involves first curing at 80-100℃ for 1-3 hours, and then controlling the heating temperature at 140-150℃ for 4-8 hours.

Citation Information

Patent Citations

  • Intumescent flame-retardant polypropylene and preparation method thereof

    CN111040293A

  • Nano-silica modified macromolecular flame-retardant charring agent and preparation method thereof

    CN112321895A